An Exploratory Study on the Anti-inflammatory Effects of Fucoidan in Relation to Quality of Life in Advanced Cancer Patients. (June 2018) - Takahashi, Hidenori; Kawaguchi, Mitsuhiko; Kitamura, Kunihiro; Narumiya, Seiji; Kawamura, Munenori; Tengan, Isamu; Nishimoto, Shinji; Hanamure, Yasuo; Majima, Yasuo; Tsubura, Shuichi; Teruya, Kiichiro; Shirahata, Sanetaka
Background. Conventional anticancer therapies still cause difficulties with selective eradication and accompanying side effects that reduce patients' quality of life (QOL). Fucoidan is extracted from seaweeds and has already exhibited broad bioactivities, including anticancer and anti-inflammatory properties, in basic studies. It is expected to enhance therapeutic efficacy and minimize side effects in cancer patients; however, despite its potential benefits, there are very few clinical trials using fucoidans. Therefore, we performed an exploratory clinical study for advanced cancer patients to examine the efficacy of fucoidans, especially focusing on inflammation in relation to QOL scores. Methods. We conducted a prospective, open-label clinical study for advanced cancer patients using fucoidans via oral administration; 20 advanced cancer patients with metastases were recruited and were given 400 mL/d fucoidan (10 mg/mL) for at least 4 weeks. Inflammatory biomarkers, including high-sensitivity C-reactive protein and various cytokines, and QOL scores were monitored before treatment, after 2 weeks, and after 4 weeks of fucoidan ingestion. Results. The main proinflammatory cytokines, including interleukin-1β (IL-1β), IL-6, and tumor necrosis factor-α (TNF-α) were significantly reduced after 2 weeks of fucoidan ingestion. QOL scores, including fatigue, stayed almost stable without significant changes during the study period. The univariate and multivariate analyses revealed that the responsiveness of IL-1β was a significant independent prognostic factor. Conclusion. This is the first study providing evidence of the anti-inflammatory effects of fucoidans for advanced cancer patients. In future studies, larger blinded, controlled trials are required to establish the efficacy of fucoidan as supportive care for cancer patients, especially those undergoing chemotherapy.